CVD Growth of a Horizontally Aligned One-Dimensional Van der Waals Material, Nb2Se9 - Lee, Sang Hoon; Jeong, Byung Joo; Choi, Kyung Hwan; Jeon, Jiho; Lee, Bom; Cho, Sooheon; Jang, Han Eol; Cho, Hyeon Ho; Oh, Hyung Suk; Kim, Bum Jun; Yu, Hak Ki; Choi, Jae Young (Crystal Growth and Design, 2023)
A one-dimensional (1D) crystal structure was grown in the edge direction to form a nanowire, similar to 2D materials grown in an edge plane with dangling bonds to form a nanosheet. In this study, Nb2Se9, a 1D van der Waals (vdW) material, was grown on a substrate using a linear physical space via a liquid-precursor-assisted chemical vapor deposition (CVD) process. Nb2Se9 nanowires grown on a millimeter scale along the scratch on SiO2 showed non-epitaxial growth, and the aligned Nb2Se9 nanowires oriented on the vicinal surface of m-plane sapphire. The density of the precursor and the flow rate of H2 gas in the CVD process could control the direction, density, and dimensions of the aligned Nb2Se9 nanowire array on the vicinal surface. Compared to other synthesis methods, aligned Nb2Se9 nanowires exhibit higher photoresponse and stability. This controllable CVD growth of aligned Nb2Se9 offers a possibility of it being used as a building block for large integrated circuits based on 1D materials.
Keywords: 1-d crystals; Chemical vapor deposition process; Chemical vapour deposition; Crystals structures; Edge direction; Liquid precursors; Millimeter-scale; One-dimensional; Van der Waal; Vicinal surface